Penyuluhan Manajemen Misi dan Pertumbuhan Gereja bagi Orang Percaya dalam Pendidikan Agama Kristen - Halim Wiryadinata; Noh Ibrahim Boiliu; Desi Sianipar; Desy Irawaty Santoso; Eklin Amtor de Fretes (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
This community service study aims to implement the discourse idea of managing mission and church growth within the Indonesian Muria Christian Church, specifically at the Ark of God. The growth of church members enables the management of the church through mission and church growth, manifesting the love of God to others. This idea reflects the most excellent command of Jesus in Matthew 28:18-20, which is the command to share our lives with others throughout the world. Therefore, the concept of mission and church growth invites management to apply knowledge in planning, implementing, and evaluating the program. This community service utilizes an outreach method to the church community. This method incorporates the results of mission management and church growth, as guided by the most excellent command of Christ. The conclusion is to present the eagerness of the church community to create the program as a practical program ahead of time.